2009
DOI: 10.1071/rdv21n1ab14
|View full text |Cite
|
Sign up to set email alerts
|

14 Sublethal Hydrostatic Pressure Treatment Improves Fresh and Chilled Boar Semen Quality in Vitro and in Vivo

Abstract: Insemination of fresh boar semen is a widely used production tool in swine breeding and meat production. Although the success rates of routine insemination procedures are satisfactory, improvements are still needed to reduce production costs; moreover, the reduced litter size of gilts compared with sows still calls for further solutions. Sublethal high hydrostatic pressure (HHP), applied to fresh boar semen before cryopreservation, was reported to improve post-thaw motility and litter size. Proteomic studies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Our data revealed that the O-E9 group increased sperm viably and therefore can be applied successfully to increase the efficiency of freeze-thawing process in bull. This observation is in line with an earlier study in which an increased sperm survival after cryopreservation or prolonged in vitro storage has been achieved by hydrostatic pressure-induced stress tolerance in bull [43] and boar [44].…”
Section: Discussionsupporting
confidence: 92%
“…Our data revealed that the O-E9 group increased sperm viably and therefore can be applied successfully to increase the efficiency of freeze-thawing process in bull. This observation is in line with an earlier study in which an increased sperm survival after cryopreservation or prolonged in vitro storage has been achieved by hydrostatic pressure-induced stress tolerance in bull [43] and boar [44].…”
Section: Discussionsupporting
confidence: 92%
“…The treatment did not increase pregnancy or farrowing rates, but a significant increase of litter size was observed. A positive effect was also demonstrated by in vitro investigations, where the lifespan of routinely stored boar semen increased after HHP treatment [13]. Further experiments have demonstrated that HHP treatment considerably improved the cryotolerance of porcine semen [14,15].…”
Section: Blastocystsmentioning
confidence: 82%
“…Up till the date of the submission of this manuscript, 491 and 155 healthy piglets were born as a result of the insemination of HHP-treated fresh or cryopreserved spermatozoa, respectively [13,16]. Piglets were not different from the control in sex ratio, weight, stillbirth, and malformations.…”
Section: In Vivo Consequencesmentioning
confidence: 99%
“…For in vitro evaluation, treated or not treated semen was kept in a cooling thermostat set to 16°C. Total and progressive motility measured at days 5 and 12 was significantly higher in the treated groups compared with control (Pribenszky et al. 2009).…”
Section: Hp Treatment Induced Increase In Cryotolerance and Performanmentioning
confidence: 78%
“…However, the effect of treatment on the litter size was significant (12.4 vs 11.4; HP treated vs non‐treated). Moreover, there was a significant difference in treatment effects between the gilts and the sows, whereas treatment had no significant effect on the litter size of the sows (p = 0.47), the litter size of the gilts increased (p < 0.001), with a mean of 2.55 ± 0.83 (SE) (Pribenszky et al. 2009).…”
Section: Hp Treatment Induced Increase In Cryotolerance and Performanmentioning
confidence: 99%